The relationship of adverse childhood experiences of pregnant women with healthy lifestyle behaviours and birth attitudes: A cross-sectional study - Esra Cevik; Pelin Palas Karaca (PLoS ONE, 2026)
Introduction This study was conducted to determine the relationship between negative childhood experiences of pregnant women and health-promoting lifestyle behaviours and childbirth attitudes. Methods The cross-sectional study was conducted with 468 pregnant women between March 2023 and January 2024. Data were collected using a descriptive characteristics form, an adverse childhood experiences questionnaire (ACEQ), a health-promoting lifestyle profile (HPLP-II), and a childbirth attitude questionnaire (CAQ). The study reporting followed the STROBE checklist. Results Participants’ mean scores were as follows: ACEQ 1.10 ± 1.84, CAQ 39.91 ± 12.18, and HPLP-II 138.64 ± 23.71. Linear regression analysis showed that HPLP-II scores were significantly lower in non-employed women ( β = −0.194; 95% CI: −14.06, −5.44; p = 0.000) and smokers ( β = −0.104; 95% CI: −12.05, −1.05; p = 0.020). Lower income perception was significantly associated with decreased HPLP-II scores ( β = −0.170; 95% CI: −11.34 to −3.48; p = 0.000). Additionally, higher ACEQ scores were also significantly related to lower HPLP-II scores (β = −0.092; 95% CI: −2.29 to −0.06; p = 0.037). Regarding CAQ, scores were significantly higher among participants with lower income perception ( β = −0.200; 95% CI: −6.35, −2.59; p = 0.000), those who consumed alcohol during pregnancy ( β = −0.322; 95% CI: −16.36, −9.70; p = 0.000), and those with higher ACEQ scores ( β = 0.158; 95% CI: 1.09, 1.58; p = 0.000). Discussion Pregnant women’s negative childhood experiences affect both birth anxiety and health-promoting lifestyle behaviours.